Comparison of the Effect of Resistance and Balance Training on Isokinetic Eversion Strength, Dynamic Balance, Hop Test, and Ankle Score in Ankle Sprain - Wang, Haifang (Life (Basel), 2021)
Ankle sprain is a commonly recurring sports injury. This study aimed to compare the rehabilitation effects of resistance and balance training programs in patients with recurrent ankle sprain. Patients with recurrent lateral ankle sprain completed a home-based rehabilitation program comprising resistance training (RT; n = 27) or balance training (BT; n = 27). RT consisted of exercises using elastic tube bands, and BT consisted mainly of exercises performed using a variety of balance tools. Exercises were performed for 6 weeks, twice a day for 20 min, 5 days per week. Isokinetic eversion strength, Y-Balance test and hop tests, and foot and ankle outcome score (FAOS) were evaluated. Both RT and BT significantly improved strength and dynamic balance (p < 0.05). Compared to RT, BT also significantly improved the outcome of the crossover hop test (p = 0.008). The changes reflected group and time in pain (p = 0.022), sports (p = 0.027), and quality of life (p = 0.033) of FAOS were significantly greater in BT than RT.